2022
DOI: 10.3390/children9050651
|View full text |Cite
|
Sign up to set email alerts
|

Medical Communication during the Transition to Palliative Care in Pediatric Oncology in Hungary—The Parents’ Perspective

Abstract: The transition to palliative care (PC) is a critical aspect of pediatric oncology, and it requires a high level of communication skills from doctors, which could be best judged by the parents of children who have died from cancer. Our aim was to explore the parents’ perspectives regarding the timing of the consultation on the implementation of PC, as well as facets of verbal and nonverbal communication in Hungary. Semistructured interviews were conducted with parents who had lost a child to cancer within the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…In another study in Hungary, the majority of parents who had lost a child said that palliative care was introduced after all possible treatments. Thus, there was a substantial gap between curative and palliative therapy [46]. This study and our present research findings highlight the discrepancy between international recommendations and current practice and draw attention to the need to rethink the concept of palliative care.…”
Section: Discussionmentioning
confidence: 55%
“…In another study in Hungary, the majority of parents who had lost a child said that palliative care was introduced after all possible treatments. Thus, there was a substantial gap between curative and palliative therapy [46]. This study and our present research findings highlight the discrepancy between international recommendations and current practice and draw attention to the need to rethink the concept of palliative care.…”
Section: Discussionmentioning
confidence: 55%
“…The quality and methods of communication with parents play an important role in the treatment of the child and have the potential to raise morale. It has been observed that the child and the parents show greater commitment to treatment when communication is better [ 8 , 25 ]. Knowing that the disease is curable, and that effective treatment is available but not affordable in all cases presents a moral challenge that requires highly effective communication.…”
Section: Discussionmentioning
confidence: 99%
“…En Hungría se realizó un estudio con padres que habían perdido un hijo por cáncer, el cual mostró que, en su mayoría, no recibieron información sobre qué podía ocurrir en un futuro o sobre a quién recurrir para obtener más información o apoyo respecto a la salud de su hijo. Aunque ha habido avances, aún no existe un método de comunicación aceptado para la transición a los cuidados paliativos (Foldesi et al, 2022).…”
Section: Rmp Y Habilidades De Comunicaciónunclassified